2023
DOI: 10.3389/fmicb.2023.1073753
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal connectivity of the aquatic microbiome associated with cyanobacterial blooms along a Great Lake riverine-lacustrine continuum

Abstract: Lake Erie is subject to recurring events of cyanobacterial harmful algal blooms (cHABs), but measures of nutrients and total phytoplankton biomass seem to be poor predictors of cHABs when taken individually. A more integrated approach at the watershed scale may improve our understanding of the conditions that lead to bloom formation, such as assessing the physico-chemical and biological factors that influence the lake microbial community, as well as identifying the linkages between Lake Erie and the surroundin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 113 publications
1
5
0
Order By: Relevance
“…At the phylum level, Proteobacteria, Bacteroidetes, Actinobacteria, Verrucomicrobia, and Firmicutes were abundant in all tested samples, consistent with other findings (surface water and sediment) for the Great Lakes region [ 24 , 52 , 53 ]. Interestingly, for Beach A, Cyanobacteria sequences were significantly more abundant in BAV non-exceedance samples than exceedance days or associated with the adjacent creek water source.…”
Section: Discussionsupporting
confidence: 90%
“…At the phylum level, Proteobacteria, Bacteroidetes, Actinobacteria, Verrucomicrobia, and Firmicutes were abundant in all tested samples, consistent with other findings (surface water and sediment) for the Great Lakes region [ 24 , 52 , 53 ]. Interestingly, for Beach A, Cyanobacteria sequences were significantly more abundant in BAV non-exceedance samples than exceedance days or associated with the adjacent creek water source.…”
Section: Discussionsupporting
confidence: 90%
“…The protocols used led to an increase in the detection specificity [239][240][241]. HAB monitoring conducted in the Ohio inland lakes (Ohio, USA) between 2020 and 2022 demonstrated that qPCR and RT-qPCR can be considered extremely useful early warning tools to characterize cyanobacterial blooms and to identify cyanotoxin production [241][242][243]. Furthermore, compared with traditional microscopy and cell counting methods, qPCR is undoubtedly more rapid, providing results in 3 h [242].…”
Section: Algae Detection Methodsmentioning
confidence: 99%
“…HAB monitoring conducted in the Ohio inland lakes (Ohio, USA) between 2020 and 2022 demonstrated that qPCR and RT-qPCR can be considered extremely useful early warning tools to characterize cyanobacterial blooms and to identify cyanotoxin production [241][242][243]. Furthermore, compared with traditional microscopy and cell counting methods, qPCR is undoubtedly more rapid, providing results in 3 h [242]. Recent advances, associating PCR techniques with high-throughput sequencing of the 16s rRNA gene (e.g., Next-Generation Sequencing), are being employed as risk assessment ameliorating strategies [243].…”
Section: Algae Detection Methodsmentioning
confidence: 99%
“…For example, high water velocity was reported to reduce microbial adhesion and the formation of biofilms relative to habitats with lower water velocities [22,24]. Microbial community connectivity fundamentally depends on the rate of microbial dispersal among patches within an environment [25,26]. Thus, high habitat connectivity (e.g., due to high water flow) is expected to result in reduced beta diversity across aquatic landscapes.…”
Section: Introductionmentioning
confidence: 99%